Full Thickness Versus Circular Peroral Myotomy in the Treatment of Esophageal Achalasia: : A Systematic Review and Meta-Analysis - Sayeh, Wasef (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.